Delaying and reversing frailty: a systematic review of primary care interventions - Travers, John; Romero-Ortuno, Roman; Bailey, Jade; Cooney, Marie-Therese (British journal of general practice, 2019)
Recommendations for routine frailty screening in general practice are increasing as frailty prevalence grows. In England, frailty identification became a contractual requirement in 2017. However, there is little guidance on the most effective and practical interventions once frailty has been identified. To assess the comparative effectiveness and ease of implementation of frailty interventions in primary care. A systematic review of frailty interventions in primary care. Scientific databases were searched from inception to May 2017 for randomised controlled trials or cohort studies with control groups on primary care frailty interventions. Screening methods, interventions, and outcomes were analysed in included studies. Effectiveness was scored in terms of change of frailty status or frailty indicators and ease of implementation in terms of human resources, marginal costs, and time requirements. A total of 925 studies satisfied search criteria and 46 were included. There were 15 690 participants (median study size was 160 participants). Studies reflected a broad heterogeneity. There were 17 different frailty screening methods. Of the frailty interventions, 23 involved physical activity and other interventions involved health education, nutrition supplementation, home visits, hormone supplementation, and counselling. A significant improvement of frailty status was demonstrated in 71% ( = 10) of studies and of frailty indicators in 69% (n=22) of studies where measured. Interventions with both muscle strength training and protein supplementation were consistently placed highest for effectiveness and ease of implementation. A combination of muscle strength training and protein supplementation was the most effective intervention to delay or reverse frailty and the easiest to implement in primary care. A map of interventions was created that can be used to inform choices for managing frailty.